Rethinking Eurovision Song Contest as a Clash of Cultures - Zeynep Merve ŞIVGIN (Gazi Akademik Bakış)
Modern era’s understanding of culture overlooked culture, as a social and cultural analysis category as well as a way of life. This point of view has lost its validity and culture gained significance as an area where rulership and power struggle exists. Especially the privileged existence of popular culture; having an interdependence attachment to power relations in addition to an allowing structure for alternative discourses other than the official discourse is a cruicial asset. This article examines Eurovision Song Contest with its over 50 years of traditionaled history, as a noteworthy television program of popular culture. Despite often being considered as “kitsch”, the contest refers more than of an ordinary song competition. The artists who participate in the contest compete for the country they represent rather than an individual race which takes “national identity” more on stage. In this respect the contest has a stimulus effect on national consciousness. This alerted effect can clearly be seen on public debates just before, during and after the contest. It is claimed in this study that Turkey’s position in Eurovision Song Contest offers a view of the “cultural struggle” towards Western civilization since the beginning of the modernization process. In this framework this study primarily focuses on the relationship between identity and culture, followed by the role of popular culture in the construction of cultural identity. Afterwards the study tries to discover how does this contest became a tool of cultural struggle in Turkish society by analyzing the news and the discource of the news that took place in national print media.